Water hazard detection: A 20-year review. (February 2023) - Guo, Xiaodong; Han, Jizhou; Li, Jingyu; Wang, Zhoubo; Zhang, Zhenhai; Kang, Xiao; Zhu, Wei; Deng, Hongbin
Highlights: The Timeline Spans a Wide Range. This paper extensively reviewed about 142 papers in the history of water hazards detection. These papers spanned 20 years. The previous papers only focused on short-term or specific tasks, and did not consider the entire long-term technological development. The Research on the Target is Relatively Detailed and Concentrated. This paper only summarizes and prospects the research on water hazards, and the work is more meticulous, while the research objectives of the previous review literature are relatively broad, which leads to the broad and rough literature arrangement. Multi-Angle Analysis of a Single Research Object. This paper classifies and sorts out the detection literature of water hazards from multiple angles. The previous review literature has a relatively single classification method for water hazards detection research. Abstract: Obstacle detection is a complex task involving detection of obstacle features, identification of appropriate sensor and environmental conditions. The development of water hazard detection in the past two decades can be regarded as a microcosm of the history of typical obstacle detection. This review provides an extensive study of water hazard detection papers spanning a quarter-century (the 1990 s to 2021). The review mainly focuses on the width of water hazards, features of water hazards, sensor types for the detection of water hazards, and environmental light. This paper analyses and summarizes the research overview and status of some research institutions in the field over the past 20 years, hoping to provide some reference for UGV water hazard detection. In addition, the existing water hazard detection problems are summarized, and future development trends are proposed.